Dignidade da pessoa humana : reflexões jurídicas e filosóficas sobre o conceito - Librelotto, Gicélia (2017)
The judicial and philosophical reflexions about the concept of Human Dignity carry the purpose of being integrated to an ancient discussion about the subject; however, their primary objective is to stimulate the amplification and modernization of this controversial issue, which is of capital importance to the preservation of life in society and the Democratic State of right, presenting exemplifying increments originated from legal and doctrinal texts. A bibliographic research method was utilized; the ana-lysis - both theoretical and doctrinal - of some of the most recognized ancient and modern concepts from prominent authors and of the dimensions accepted by the "Human Dignity" expression; social and judicial facts, as well as legal and constitu-tional materials, with an emphasis on the difficulty of the creation of a universal concept. The result of the research shows that, regardless of the existence of a universal concept, the interpretation of this expression is, across history, worldwide known, presenting meanings that are analogous, although not uniform. This project conclu-des that, despite the absence of a general agreement about the meaning and inter-pretation of the expression "Human Dignity", primarily considering the difficulty in conceptualizing terms that have a substantial philosophical and axiological signi-ficance, urges not only the search for a concept but, above that, the revelation and awareness of this idea, whose nucleus is human condition itself.